Penerapan Metode K-Medoids untuk Menentukan Status Gizi Balita di Puskesmas Dermayu - Alon Santoso; Indra Kanedi; Deri Lianda (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
The nutritional condition of children under five is one of the parameters of the state of public health in each region. Good nutrition in toddlers has an important influence on normal growth, physical development and intelligence in children, with good nutrition the body is not easily attacked by disease, infection, and is protected from chronic diseases. So there is a need for a system to find out the nutritional status of toddlers in a region as a source of information. input for the government and policy holders in the field of public health to prevent and overcome malnutrition in children under five.This research applies data mining for clustering the nutritional status of toddlers at the Dermayu Community Health Center using the K-Medoids algorithm method. This research method uses the waterfall method.Based on the results of this research, the nutritional status values of toddlers at the Dermayu Community Health Center can be clustered using the K-Medoids algorithm through two parameters: Toddler Weight (BB) and Toddler Height (TB), which are divided into 5 clusters, namely obesity, over nutrition, good nutrition, malnutrition and malnutrition to help the performance of community health centers and parents of toddlers in early handling of toddlers' nutritional conditions. From these results, it is known that there are still 30% of toddlers who are obese and 11% of toddlers who are malnourished, so there is a need for assistance from the relevant health centers for parents of toddlers so that the number of toddlers who are malnourished can decrease in the following year.